Extensive genotype-phenotype heterogeneity in renal cell carcinoma - a proof-of-concept study - Jakob Wieke; Christina Jurcic; Adam Kaczorowski; Sarah Böning; Martina Kirchner; Constantin Schwab; Viktoria Schütz; Markus Hohenfellner; Anette Duensing; Albrecht Stenzinger; Stefan Duensing (Frontiers in Oncology)
BackgroundRenal cell carcinoma (RCC) is characterized by a high degree of genomic but also functional intratumoral heterogeneity (ITH). Mutations in VHL, chromatin remodeling genes such as SETD2 and genes that regulate the PI3K/AKT/mTOR pathway have been identified as recurrent drivers despite genomic ITH. Whether and to what extent these mutations shape functional ITH including the formation of spatial niches is incompletely understood. Herein, we analyze the correlation between mutational drivers and their functional proxies in a spatially defined manner.MethodsA total of 23 RCCs were analyzed by panel next-generation sequencing followed by immunohistochemistry for five functional proxies for key genetic alterations including the expression of CD31, GLUT1, phospho-mTOR S2448, H3K36me3 and Ki-67. Antibody stainings were scored semiquantitatively in the tumor periphery and the tumor center.ResultsUnexpectedly, the presence of a VHL mutation was not found to correlate with its functional proxies including the expression of CD31/microvessel density or the expression of the glucose transporter GLUT1. Likewise, there was no correlation between the presence of activating mutations in genes of the PI3K/AKT/mTOR pathway and the expression of activated phospho-mTOR S2448. Furthermore, mutations in the methyltransferase gene SETD2 were not found to correlate with the expression level of its downstream target H3K36me3. Lastly, there was no correlation between the expression of the proliferation marker Ki-67 and the number of driver mutations.ConclusionThis proof-of-concept study adds genotype-phenotype heterogeneity as additional layer of complexity to the known genomic and functional ITH in RCC.